Improving Online Learning through the Use of Learning Management System Platform: A Technology Acceptance Model-Technology Readiness Index Combination Model Approach - Mufidah, Ilma; Husaini, Luthfi Romiz; Caesaron, Dino (Institute of Research and Community Outreach - Petra Christian University, 2022)
The COVID-19 pandemic push the learning revolution. The previous onsite learning is suddenly change to online learning. Current technological developments support the online learning application through the use of Learning Management System Platform. However, some problems are found during the application of online learning. Thus, this research aims to improve online learning through the use of Learning Management System Platform. The Technology Acceptance Model and the Technology Readiness Index model were combined to identify the critical factors influencing the intention to use Learning Management System. Fourteen hypotheses were proposed and tested using the Structural Equation Modelling method run in Partial Least Square software. The results indicated that eight hypotheses were accepted. The accepted hypothesis represents the criticality to consider innovativeness, job relevance, perceived enjoyment, perceived security and subjective norm in the Learning Management System usage during online learning during the COVID-19 Pandemic